Sinkronisasi System Perdamaian Khusus Tindak Pidana Pencurian Kelapa Sawit di Wilayah Polsek Bahar Selatan Melalui Hukum Adat Setempat dan Hukum Positif Indonesia - Nggeboe, Ferdricka; Ibrahim, Ibrahim; Putra, Yohanes Chandra (Legalitas: Jurnal Hukum, 2023)
Palm oil theft was resolved in a customary manner by the people of Bahar Selatan Muara Jambi rather than through the criminal justice system starting from the Bahar Selatan Police so they were interested in doing research. The aim of the research is to understand and analyze the Settlement of Criminal Cases according to Selata customary law, to examine the actions and efforts in the jurisdiction of the Bahar Police, the research method uses empirical juridical. Completion of Criminal Cases Based on Customary Law in the Legal Area of the South Bahar Police with customary institutions at the sub-district level of South Bahar on the basis of considerations of theft caused by the difficulty of finding work, due to the number of residents who do not match employment opportunities, the large number of people who drop out of school, because of school graduation certificates is a formal requirement for finding a job. Therefore people use shortcuts, namely working a little and making a lot of money. even if you commit an unlawful crime of theft. The Attitudes and Actions of the Police of the Bahar Selatan Police on the Report on Completion of Criminal Theft according to Customary Law while continuing to carry out the minutes through the restorative justice process and the results of peace through adat as a witness to the tuo tengganai traditional institutions of the South Bahar Sub-District The efforts of the South Bahar Police in Providing an Understanding of the Synchronization of Local Customary Law and Indonesian Positive Law in Enforcing the Criminal Law of Palm Oil Theft in the South Bahar Police Area through outreach through socialization by providing an understanding of procedures Guidelines for the mechanism for implementing restorative justice in Enforcing the Criminal Law of Palm Oil Theft in the South Bahar Police Area the suggestion put forward is that involvement is needed the community, traditional institutions and stakeholders of Bahar Selatan in carrying out the settlement of criminal cases of theft, bearing in mind that the community (environment) is an object that is directly affected by a crime, and also that the community can participate in the settlement process from start to finish, such as: restoration of rights victims and vindication of perpetrators. Simultaneous increase in police officers carrying out socialization in the midst of society the importance of restorative justice in the context of synchronizing peace with traditional institutions.